Measurement of glomerular filtration rate and its current status in African countries: GFR measurement and its status in Africa - Holness, Jennifer L; van der Westhuizen, Diederick J; Davids, M Razeen; Warwick, James M (African Journal of Nephrology, 2022)
Glomerular filtration rate (GFR) is usually estimated rather than measured as this only requires measurement of an endogenous filtration marker. In certain clinical settings a more accurate measure of GFR is essential. The most commonly used endogenous filtration marker is creatinine. Exogenous filtration markers include nonradiopharmaceuticals such as inulin, iohexol and unlabelled iothalamate, or radiopharmaceuticals such as 51Crethylenediaminetetraacetic acid (51Cr-EDTA) and 99mTc-diethylenetriaminepentaacetic acid (99mTc-DTPA). Inulin is considered an ideal filtration marker but the clearance of iothalamate, 99mTc-DTPA, 51Cr-EDTA and iohexol have all been shown to have sufficient accuracy for measuring GFR. For radiopharmaceuticals, a well counter is required to measure the amount of activity in patient samples. Iohexol or unlabelled iothalamate require samples to be measured using high performance liquid chromatography with ultraviolet detection (HPLC-UV), liquid chromatography-tandem mass spectrometry (LC-MS/MS) or x-ray fluorescence (XRF). Due to the practical challenges of measuring urinary clearance, measurement of GFR in clinical settings is almost exclusively based on plasma clearance of a filtration marker. This can follow a long-established approach based on the ratio of the tracer administered to the area under the plasma concentration curve. Alternatively, a single plasma sample giving an apparent volume of distribution at a given time point can be used to accurately measure GFR. While techniques exist for the measurement of GFR in a number of African countries, preliminary evidence suggests that facilities are very limited. There is a need for support for both equipment and training to establish GFR measurement facilities in several centres on the continent.